Monoclonal Antibodies Specific to the Extracellular Domain of Histidine Kinase YycG of Staphylococcus epidermidis Inhibit Biofilm Formation - Lyu, Zhihui; Shang, Yongpeng; Wang, Xiaofei; Wu, Yang; Zheng, Jinxin; Liu, Huayong; Gong, Ting; Ye, Lina; Qu, Di (Frontiers in Microbiology, 2020)
Staphylococcus epidermidis is frequently associated with biofilm-related infections. Biofilms drastically reduce the efficacy of conventional antibiotics and the host immune system. In S. epidermidis biofilm formation, a major role is played by the YycG/YycF two-component system, and previous findings have indicated that inhibitors targeting the cytoplasmic HATPase_c domain of YycG kinase in S. epidermidis exhibit bactericidal and biofilm-killing activities. Therefore, we hypothesized that monoclonal antibodies (mAbs) against YycG extracellular (YycGex) domain would block the signal transduction and influence the biofilm formation of S. epidermidis. In this study, we screened out two YycGex-specific mAbs showing the highest affinity for the target, mAbs 2F3 and 1H1. These mAbs inhibited S. epidermidis biofilm formation in a dose-dependent manner, and at a concentration of 160 μg/mL, mAbs 2F3 and 1H1 caused 78.3% and 93.1% biofilm reduction, respectively, relative to normal mouse IgG control. When co-cultivated with YycGex mAbs, S. epidermidis cells showed diminished initial-adherence capacity, and the antibody treatment further led to a marked decrease in the synthesis of polysaccharide intercellular adhesin and in the transcriptional level of genes encoding proteins involved in biofilm formation. Lastly, we determined that the epitopes recognized by the two YycGex mAbs are located within aa 59–70 of YycGex domain. It indicates that YycGex domain may be a potential candidate as a vaccine for the prevention of S. epidermidis biofilm infections.